2021
DOI: 10.3389/fonc.2021.722961
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomography-Based Radiomics in Predicting T Stage and Length of Esophageal Squamous Cell Carcinoma

Abstract: BackgroundBecause of the superficial and infiltrative spreading patterns of esophageal squamous cell carcinoma (ESCC), an accurate assessment of tumor extent is challenging using imaging-based clinical staging. Radiomics features extracted from pretreatment computed tomography (CT) or magnetic resonance imaging have shown promise in identifying tumor characteristics. Accurate staging is essential for planning cancer treatment, especially for deciding whether to offer surgery or radiotherapy (chemotherapy) in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…The clustering findings revealed that it could be classified into 38 groups, yet only the top 14 were shown in Figure 7A . The largest cluster was “radiomics” (#0) ( 53 56 ), while “tumor segmentation”(#6) ( 57 – 61 )was the earliest research in this field. “Endoscopy” (#9) ( 62 65 ) and “deep learning” (#2) ( 66 70 ) were the latest research hotspots.…”
Section: Resultsmentioning
confidence: 99%
“…The clustering findings revealed that it could be classified into 38 groups, yet only the top 14 were shown in Figure 7A . The largest cluster was “radiomics” (#0) ( 53 56 ), while “tumor segmentation”(#6) ( 57 – 61 )was the earliest research in this field. “Endoscopy” (#9) ( 62 65 ) and “deep learning” (#2) ( 66 70 ) were the latest research hotspots.…”
Section: Resultsmentioning
confidence: 99%
“…Our CT test model showed an AUC of 0.96 (95% CI 0.87–1.00). The results were slightly better than the radiomics model developed by Yang et al (AUC 0.857; 95% CI 0.691–1.000) [ 26 ]. In another study, Wu et al used a radiomics approach to identify early- and late-stage ESCC prior to surgery [ 17 ].…”
Section: Discussionmentioning
confidence: 57%
“…Published studies have mainly investigated the predictive ability of radiomics in the staging, therapy response, and postoperative recurrence of EC[ 16 - 19 ].…”
Section: Radiomics Workflowmentioning
confidence: 99%
“…Radiomic characteristics based on CT have good predictive potential for EC staging[ 20 , 21 ]. Yang et al [ 19 ] reported that CT radiomic characteristics were significantly correlated with the tumor (T) stage and tumor length of EC and showed good predictive performance for both; the area under the ROC curve (AUC), sensitivity, and specificitywere 0.86, 0.77 and 0.87, respectively, and 0.95, 0.92 and 0.91. Radiomic features also have good efficacy in predicting EC lymphatic metastasis[ 7 , 22 - 24 ].…”
Section: Radiomics Workflowmentioning
confidence: 99%